2018
DOI: 10.1002/smi.2813
|View full text |Cite
|
Sign up to set email alerts
|

Children's stress‐related reports and stress biomarkers interact in their association with metabolic syndrome risk

Abstract: The purpose was to examine the cross-sectional associations of stress-related reports and stress biomarkers with metabolic syndrome (MetS) risk in children while also testing the interaction between stress biomarkers and stress reports. In 353 children (5-10 years old, 7.9% overweight/obese), MetS risk was measured by blood pressure, waist circumference, glucose homeostasis, triglycerides, and high-density cholesterol. Stress was measured by stress-related reports (events, emotions, and internalizing/externali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Three studies showed significant negative associations with SDNN and rMSSD [ 16 , 19 , 20 ]. Three studies showed significant positive associations with the LF/HF ratio [ 6 , 16 , 20 ]. On the other hand, two studies [ 16 , 27 ] showed significant positive and two studies [ 19 , 20 ] reported negative significant associations with LF.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies showed significant negative associations with SDNN and rMSSD [ 16 , 19 , 20 ]. Three studies showed significant positive associations with the LF/HF ratio [ 6 , 16 , 20 ]. On the other hand, two studies [ 16 , 27 ] showed significant positive and two studies [ 19 , 20 ] reported negative significant associations with LF.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported significant negative associations with both LF and SDNN [ 17 , 19 ]. Two studies [ 17 , 19 ] reported a significant positive association and one study [ 6 ] reported a significant negative association with LF/HF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence of the worldwide obesity epidemic, metabolic disturbances such as dyslipidemia, hypertension, and insulin resistance are on the rise already in childhood and adolescence and the prevalence of metabolic syndrome (MetS) in children is also increasing [ 1 ]. Lifestyle factors such as a high consumption of processed and snack foods and a low consumption of vegetables and wholemeal products [ 2 , 3 ], lack of physical activity (PA), high levels of media use and sedentary behaviors (SB) [ 4 , 5 ] as well as low well-being e.g., due to psychosocial stress [ 6 , 7 ] are associated with an increased risk for overweight, obesity and metabolic disturbances. Apart from lifestyle, non-modifiable 1 risk factors such as family history of MetS components, parental education, maternal body mass index (BMI), breastfeeding duration, birth weight as well as pubertal development also influence the risk of metabolic disturbances [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%